Interview with Assar Lindbeck - Thorvaldur Gylfason (Center for Economic Studies and ifo Institute (CESifo), 2005)
Macroeconomic Dynamics commissioned this interview with Assar Lindbeck for a series of such conversations with economists, starting with Duncan Foley's interview with Wassily Leontief in 1998. Other interviews in the series include Ben McCallum's interview with Robert Lucas (1999), Olivier Blanchard's interview with Janos Kornai (1999), Daniel Trefler's interview with Elhanan Helpman (1999), William Barnett and Robert Solow's interview with Franco Modigliani (2000), John Taylor's interview with Milton Friedman (2001), James Poterba's interview with Martin Feldstein (2003), Brian Snowdon's interview with Axel Leijonhufvud (2003), William Barnett's interview with Paul Samuelson (2003), and John Campbell's interview with Robert Shiller (2004). Forthcoming interviews include Olivier Blanchard's interview with Stanley Fischer (2005), Omar Licandro and Pierre Dehez's interview with Jacques Dr?ze (2005), and George Evans and Seppo Honkapohja's interview with Tom Sargent (2005).
Keywords: A10; 330; Endogenous politicians; incentive problems; social norms; welfare state; unemployment; Wirtschaftswissenschaftler; Persönlichkeiten; Wissenschaft; Wirtschaftswissenschaft; Schweden; Lindbeck Assar